2021
DOI: 10.22358/jafs/138774/2021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different selenium sources on sow reproductive performance and piglet development: a meta-analysis

Abstract: Selenium is an essential trace element for pig growth; generally, inorganic or organic selenium is used for dietary selenium supplementation. Newborn piglets obtain all nutrients from the sow; thus, the sow absorption rate of different selenium sources significantly affects sow reproductive performance and piglet development. Therefore, a meta-analysis was performed to provide insights into whether organic selenium is better than mineral selenium for improving sow reproductive performance and piglet developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…A similar result was reported in another study where growing pigs fed L-SeMet had the highest ( P < 0.05) tissue Se concentration, followed by Se yeast and then sodium selenite ( Falk et al, 2018 ). In a meta-analysis, Zhou et al (2021) observed that sows fed organic Se sources had 29% greater serum Se concentration than inorganic Se sources. However, we observed no evidence of difference in pigs fed Se yeast compared to sodium selenite.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar result was reported in another study where growing pigs fed L-SeMet had the highest ( P < 0.05) tissue Se concentration, followed by Se yeast and then sodium selenite ( Falk et al, 2018 ). In a meta-analysis, Zhou et al (2021) observed that sows fed organic Se sources had 29% greater serum Se concentration than inorganic Se sources. However, we observed no evidence of difference in pigs fed Se yeast compared to sodium selenite.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, pigs have lower feed intake in commercial facilities compared to research facilities; thus, the magnitude of the bioavailability of Se sources may play a more important role in commercial facilities. In a meta-analysis, the authors observed that sows fed organic Se sources had 6.4% higher GSH-Px activity than inorganic Se sources ( Zhou et al, 2021 ). This consistent improvement may be because sows are under constant oxidative stress during gestation and lactation; therefore, the increase in tissue Se level from organic Se may benefit the antioxidant status and performance of the animals ( Zhou et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, there are nutritional strategies that can attenuate the deleterious effects of thermal and oxidative stress in swine matrices of modern strains, with several studies having been carried out in recent years, focusing on substances with antioxidant capacity, such as selenium (Se) and vitamin E (Chen et al, 2016; Zhou, Xu, Liu, & Zhang, 2021).…”
Section: Introductionmentioning
confidence: 99%